2003
DOI: 10.3136/fstr.9.62
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Digestibility and Fermentation of Mannooligosaccharides from Coffee Mannan

Abstract: Digestibility of mannooligosaccharides obtained from thermal hydrolysis of spent coffee grounds was examined by in vitro digestion method. Mannooligosaccharides were resistant to human salivary ␣-amylase, artificial gastric juice, porcine pancreatic enzymes and rat intestinal mucous enzymes. Fermentation products of mannooligosaccharides in human large intestine were estimated by in vitro fecal incubation method. Mannooligosaccharides were fermented by human fecal bacteria and the products of fermentation were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
46
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 79 publications
(48 citation statements)
references
References 12 publications
2
46
0
Order By: Relevance
“…A similar enlargement of the cecum was observed in rats fed a xylooligosaccharide diet (Campbell et al, 1997) or a galactooligosaccharide diet (Tsuchihashi et al, 1988;Djouzi & Andrieux, 1997). MOS are also indigestible oligosaccharides (Asano et al, 2003). It is assumed that the cecum of rats consuming a MOS diet enlarges: the cecum weight of rats fed a MOS diet tended to enlarge compared with those fed a control diet.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…A similar enlargement of the cecum was observed in rats fed a xylooligosaccharide diet (Campbell et al, 1997) or a galactooligosaccharide diet (Tsuchihashi et al, 1988;Djouzi & Andrieux, 1997). MOS are also indigestible oligosaccharides (Asano et al, 2003). It is assumed that the cecum of rats consuming a MOS diet enlarges: the cecum weight of rats fed a MOS diet tended to enlarge compared with those fed a control diet.…”
Section: Discussionmentioning
confidence: 61%
“…Oligosaccharides Mannooligosaccharides were prepared as described in a previous paper (Asano et al, 2003). Spent coffee grounds were hydrolyzed in a reactor that was kept at 220'C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, MOS were resistant to digestive enzymes and were fermented by human fecal bacteria. The fermentation products were short chain fatty acids (SCFA) (Asano et al, 2003). These results suggested that MOS were indigestible saccharides, which were selectively utilized by beneficial bacteria and converted to SCFA in the human large intestine.…”
mentioning
confidence: 82%
“…Preparation of mannooligosaccharides (Asano et al, 2003) The thermally hydrolyzed product from spent coffee grounds was decolorized using active carbon powder (Umehachi; Taihei Chemicals, Osaka) and desalted using cation exchange resin (SKIB; Mitsubishi Chemicals) and anion exchange resin (WA30; Mitsubishi Chemicals, Tokyo). One hundred grams of a mixture of monosaccharides and MOS mixture were obtained from 300 g of the hydrolyzed products of spent coffee grounds.…”
Section: Methodsmentioning
confidence: 99%